Question #3ecb0

1 Answer
Oct 3, 2017

We can prove this using mathematical induction.
The answer got too lengthy and there will be some improvement.

Explanation:

[Part 1] Base case(n=2)
To show that the recurrence is true for n=2 we have to evaluate L_1, L_2, K_1 and K_2.

K_1=L_1=3 is obvious, as there are only three string: (0) (1) (2).

K_2=6 because the 2-words string from the set {0,1,2} in which the two maximum blocks have single word are
(0,1) (0,2) (1,0) (1,2) (2,0) (2,1).

L_2=7, as all strings without adjacent 0 and 2 are
(0,0),(0,1),(1,0),(1,1),(1,2),(2,1),(2,2)

Thus, L_2=K_2+1/3K_1 is true.

[Part 2]
What we need to do is to find a recurrence for K_n (n>=3) .

This part is long, so I posted it in another article.
https://socratic.org/questions/what-is-the-recurrence-formula-for-k-n-k-n-is-the-number-of-strings-a-1-a-2-a-n-

The result is K_1=3, K_2=6, K_n=2K_(n-1)+K_(n-2)" "(n>=3)

[Part3] Then we are going to find the recurrence of L_n (n>=3) .
Again, I posted it in another article.
https://socratic.org/questions/what-is-the-recurrence-formula-for-l-n-l-n-is-the-number-of-strings-a-1-a-2-a-n--2
The result is L_1=3, L_2=7, L_(n+1)=2L_n+L_(n-1)" "(n>=2)

[Part 4] This is the main section of mathematical induction. (n=k->n=k+1)

Suppose that L_k=K_k+1/3K_(k-1) is true for a certain k>=2.
Using the recurrences in Part 2 and Part 3:
L_(k+1)=2L_k+L_(k-1)
=2(K_k+1/3K_(k-1))+(K_(k-1)+1/3K_(k-2))
=2K_k+5/3K_(k-1)+1/3K_(k-2)

K_(k+1)+1/3K_k=(2K_n+K_(n-1))+1/3(2K_(n-1)+K_(n-2))
=2K_k+5/3K_(k-1)+1/3K_(k-2)

We reached L_(k+1)=K_(k+1)+1/3K_(k) at last!

[Part 1] and [Part 4] ensure that the proof is completed.